Adsorption of arsenic from micro-polluted water by an innovative coal-based mesoporous activated carbon in the presence of co-existing ions. (August 2015) - Gong, Xu-Jin; Li, Wei-Guang; Zhang, Duo-Ying; Fan, Wen-Biao; Zhang, Xin-Ran
Abstract: A novel, multi-step procedure was introduced to prepare an innovative coal-based activated carbon (M-NCPAC) in the present work. The adsorption characteristics of As(III)/As(V) ions in low concentrations (0.5 mg/L) from an As(III)/As(V) system were studied at 4 °C. The effects of co-existing Cr(VI) on arsenic adsorption by M-NCPAC were also determined as a function of pH, contact time and adsorbent dose in an arsenic-Cr(VI) system. The results suggested that M-NCPAC has well-developed porosity and absorption ability, such as high pore volume (1.1495 cm 3 /g), mesoporosity (64.22%), iodine numbers (1137 mg/g), and methylene blue (244 mg/g). The optimum pH for arsenic adsorption was identified as 6. M-NCPAC was proven to be a promising adsorbent (Qm, As(III)  = 1.634 mg/g, Qm, As(V)  = 1.701 mg/g) in the As(III)/As(V) system. Arsenic adsorption was suppressed in the arsenic-Cr(VI) system, and Qm, As(III) and Qm, As(V) at the optimum pH decreased by 18.23% and 11.06%, respectively. Arsenic adsorption on M-NCPAC in different systems obeyed the pseudo-second-order equation. The effects of four anions on arsenic adsorption were also evaluated either in an As(III)/As(V) system or in an arsenic-Cr(VI) system. The degrees of influence on arsenic adsorption decreased in the following order: phosphate > silicate > carbonate > sulfate. However, chromium species lowered the competitive adsorption between arsenic species and co-existing anions in the arsenic-Cr(VI) system. Highlights: New carbon (M-NCPAC) with well-developed porosity was prepared by a novel procedure. M-NCPAC was a promising adsorbent with high adsorption capacities for arsenic ions. Presence of chromium species resulted in decreasing of arsenic adsorption capacities. Phosphate competed more strongly with As(III) than with As(V). Competition between arsenic and co-existing anion was lower in Arsenic-Cr(VI) system.